Extremely Efficient Liquid Exfoliation and Dispersion of Layered Materials by Unusual Acoustic Cavitation - Han, Joong Tark; Jang, Jeong In; Kim, Haena; Hwang, Jun Yeon; Yoo, Hyung Keun; Woo, Jong Seok; Choi, Sua; Kim, Ho Young; Jeong, Hee Jin; Jeong, Seung Yol; Baeg, Kang-Jun; Cho, Kilwon; et al. (NATURE PUBLISHING GROUP, 2014)
Layered materials must be exfoliated and dispersed in solvents for diverse applications. Usually, highly energetic probe sonication may be considered to be an unfavourable method for the less defective exfoliation and dispersion of layered materials. Here we show that judicious use of ultrasonic cavitation can produce exfoliated transition metal dichalcogenide nanosheets extraordinarily dispersed in non-toxic solvent by minimising the sonolysis of solvent molecules. Our method can also lead to produce less defective, large graphene oxide nanosheets from graphite oxide in a short time (within 10 min), which show high electrical conductivity (>20,000 S m(-1)) of the printed film. This was achieved by adjusting the ultrasonic probe depth to the liquid surface to generate less energetic cavitation (delivered power similar to 6 W), while maintaining sufficient acoustic shearing (0.73 m s(-1)) and generating additional microbubbling by aeration at the liquid surface.
Keywords: GRAPHENE